2012
DOI: 10.1111/j.1442-200x.2012.03724.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia among severely malnourished children with sepsis in Bangladesh

Abstract: HP is common among children with sepsis. Potassium <2.5 mmol/L upon admission is considered a risk factor for moderate or severe HP in children with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Shoshimatsu et al, (using standard Dhaka protocol-phosphorous content not known) have reported hypophosphatemia in 14% at discharge. 4 When using premix F100 containing 579 mg phosphorus/L as per new UN specification the prevalence of hypophosphatemia at discharge was 6% as per Namusoke et al 8 This variation could be due to loss of follow up at discharge(40-48%) in both these studies. However, in present study authors have analyzed only those for whom S phosphorous is available at all three points of time.…”
Section: Changes During Treatmentmentioning
confidence: 87%
See 4 more Smart Citations
“…Shoshimatsu et al, (using standard Dhaka protocol-phosphorous content not known) have reported hypophosphatemia in 14% at discharge. 4 When using premix F100 containing 579 mg phosphorus/L as per new UN specification the prevalence of hypophosphatemia at discharge was 6% as per Namusoke et al 8 This variation could be due to loss of follow up at discharge(40-48%) in both these studies. However, in present study authors have analyzed only those for whom S phosphorous is available at all three points of time.…”
Section: Changes During Treatmentmentioning
confidence: 87%
“…The prevalence of hypophosphatemia at admission in malnourished children has been reported as 86% by Kimutai et al,72.9% by Shoshimatsu et al, 37% by Namusoke et al, respectively. 3,4,8 This variation may be due to differences in dietary intake, cut off limits for hypophosphatemia and laboratory method of estimation.…”
Section: S-phosphate At Admissionmentioning
confidence: 99%
See 3 more Smart Citations